PROBLEM OF EXPERIENCE IN POSTMODERN PHILOSOPHY ПРОБЛЕМА ОПЫТА В ПОСТМОДЕРНИСТСКОЙ ФИЛОСОФИИ ПРОБЛЕМА ДОСВІДУ В ПОСТМОДЕРНІСТСЬКІЙ ФІЛОСОФІЇ - О. Lauta (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The article is devoted research of a philosophical problematics of formation of experience during a postmodern epoch. It is analyzed structuralist strategy of an explication of experience which are directed on disclosing of manuals logocentrism and revealing anthropological character of the nature of experience. Статья посвящена исследованию философской проблематики формирования опыта в эпоху постмодерна. Проанализированы структуралистские стратегии экспликации опыта, которые направлены на раскрытие наставлений логоцентризма и виявление антропологического характера природы опыта. Стаття присвячена дослідженню філософської проблематики щодо формування досвіду в епоху постмодерну. Проаналізовані структуралістські стратегії експлікації досвіду, які спрямовані на викриття настанов логоцентризму та виявлення антропологічного характеру природи досвіду.